(untitled) (Research, Society and Development, 2024)
Technical Assistance is one of the bases for public policies to encourage production and reduce costs in family farming. Understanding this guided the action research carried out by teachers and students from IFMT, Campus Várzea Grande, MT, Brazil, together with a milk processing cooperative, COOPERGRANDE. The objective was to present the importance of public technical assistance for the verticalization of milk production, which could reduce the cooperative’s transaction costs, by expanding ties between the cooperative and its members, strengthened by close relationships. The methodology used was action research and the results obtained demonstrated that technical assistance, as a public policy, offered by EMPAER, is deficient, mainly due to lack of government investment. It is concluded that the objective was partially achieved, because despite the trust established between the cooperative members and the team of teachers and students, there was an absence of local public authorities in the training and monitoring carried out by the interveners.